Renovation Of Wastes By Mine Tailings Ponds - Leland L. Mink; Roy E. Williams; Alfred T. Wallace; Lewis M. McNay (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1973)
In 1968 the metal-mining industry of northern Idaho installed tailings ponds as a means of handling and treating mine wastes, metallurgical process wastes and domestic wastes. The installation of the ponds constituted a crash program to minimize pollution of the Coeur d'Alene River. The ponds provided an opportunity to investigate which combinations of wastes tailings ponds can be treated. The research data pertaining to tailings pond discharge lends insight into compliance with the recent EPA guideline for effluent quality.